Usaha untuk Mempertahankan Jaringan Gigi yang Sehat dalam Menanggulangi Lesi Karies dengan Konsep Pendekatan Preventif - Edi Hartini Sundoro (Journal of Dentistry Indonesia, 2015)
Recommendation that a preventive and less invasive approach has been developed. The consequences are that new concepts in the treatment of caries lesion has also been proposed. In these new concepts preservation of healthy tooth structure should be emphasized. With regard to these new concepts treatment of initial caries lesion, minimal and tunnel preparation, preventive resin restoration and atraumatic restorative treatment will be reviewed.